Formulation and development of a self-nanoemulsifying drug delivery system of irbesartan - Patel, Jaydeep (Medknow Publications Pvt Ltd, 2011)
Irbesartan (IRB) is an angiotensin II receptor blocker antihypertensive agent. The aim of the present investigation was to develop a self-nanoemulsifying drug delivery system (SNEDDS) to enhance the oral bioavailability of poorly water-soluble IRB. The solubility of IRB in various oils was determined to identify the oil phase of SNEDDS. Various surfactants and co-surfactants were screened for their ability to emulsify the selected oil. Pseudoternary phase diagrams were constructed to identify the efficient self-emulsifying region. The optimized SNEDDS formulation contained IRB (75 mg), Cremophor(®) EL (43.33%), Carbitol(®) (21.67%) and Capryol(®) 90 (32%). SNEDDS was further evaluated for its percentage transmittance, emulsification time, drug content, phase separation, dilution, droplet size and zeta potential. The optimized formulation of IRB-loaded SNEDDS exhibited complete in vitro drug release in 15 min as compared with the plain drug, which had a limited dissolution rate. It was also compared with the pure drug solution by oral administration in male Wister rats. The in vivo study exhibited a 7.5-fold increase in the oral bioavailability of IRB from SNEDDS compared with the pure drug solution. These results suggest the potential use of SNEDDS to improve dissolution and oral bioavailability of poorly water-soluble IRB.